Hospitalizations and Clinical Outcome in Metastatic Colorectal Cancer During Regorafenib or TAS-102 Therapy - Huemer, Florian (Cancers (Basel), 2020)
SIMPLE SUMMARY: Regorafenib and TAS-102 showed a survival benefit against placebo, and both drugs are approved for the treatment of metastatic colorectal cancer (mCRC) beyond second-line. The highly differential toxicity profile of both substances has led to a potentially biased perception of drug tolerability and complications—such as hospitalization—in the oncologic community. The aim of this retrospective analysis was to investigate hospitalization frequency during regorafenib and TAS-102 treatment and the impact of hospitalizations on survival. Treatment with regorafenib as well as a low Eastern Cooperative Oncology Group (ECOG) performance status turned out to be independent risk factors for hospitalization. Hospitalizations due to gastrointestinal toxicity were only seen with regorafenib. However, hospitalizations during regorafenib or TAS-102 treatment did not impact survival. In light of increased gastrointestinal toxicity leading to hospitalization during regorafenib treatment, we call for increased awareness to drug-specific toxicities, in order to prevent unnecessary complications by the early detection of adverse events and prompt counteraction. ABSTRACT: Current National Comprehensive Cancer Network (NCCN) and European Society of Medical Oncology (ESMO) guidelines recommend regorafenib or trifluridine/tipiracil (TAS-102) for the third-line therapy of metastatic colorectal cancer (mCRC). In this analysis, we evaluated hospitalizations during regorafenib or TAS-102 treatment and the impact of hospitalizations on overall survival (OS). This retrospective analysis was based on unselected, consecutive mCRC patients treated with regorafenib and/or TAS-102 at the tertiary cancer centers in Salzburg and Wels-Grieskirchen, Austria. Between January 2013 and May 2019, 93 patients started third- or fourth-line therapy with regorafenib or TAS-102. Tumor therapy (regorafenib versus TAS-102, HR: 1.95 [95% CI: 1.07–3.54], p = 0.03) and the Eastern Cooperative Oncology Group (ECOG) performance status (2–3 versus 0–1, HR: 4.04 [95% CI: 2.11–7.71], p < 0.001) showed a statistically significant association with hospitalization risk in multivariate analysis. The corresponding hospitalization probability from initiation of third- or fourth-line was 30% with regorafenib versus 18% with TAS-102 at five weeks and 41% versus 28% at ten weeks, respectively. Hospitalizations irrespective of cause during regorafenib or TAS-102 therapy did neither impact median survival in patients undergoing only third-line therapy (never-hospitalized: 5.7 months [95% CI: 3.9–10.5] versus hospitalized: 5.4 months [95% CI: 2.8–9.6], p = 0.45), nor in patients receiving third- and fourth-line therapy (12.2 months [95% CI: 10.6–28.8] versus 18.6 months [95% CI: 6.3-not reached], p = 0.90). In conclusion, apart from poor ECOG performance status, regorafenib therapy was associated with an increased hospitalization probability during palliative systemic third- and fourth-line therapy in mCRC. However, hospitalizations during regorafenib or TAS-102 therapy did not impact OS beyond second-line therapy.